A gentle introduction to stata - Acock, Alan C., 1944- (College Station, Texas : Stata Press, 2023)
"The revised sixth edition has been updated to Stata 17, including S tata command syntax, updated output, and all screenshots of Stata's int erface. Discussion and ex- amples include new features added to Stata s ince Stata 15, including the new table command, the collect suite of co mmands for creating, customizing, and exporting tables, and the use of transparencies in graphs"--
Revised edition of: A gentle introduction to Stata / Alan C. Acock. 6th edition. 2018.
"First edition 2006, Second edition 2008, Third edition 2010, Revise d third edition 2012, Fourth edition 2014, Fifth edition 2016, Sixth ed ition 2018, Revised sixth edition 2023."
Includes bibliographical references (pages 545-549) and indexes.
Keywords: Stata -- Handbooks, manuals, etc; Social sciences -- Statistics -- Computer programs; Social sciences -- Statistical methods -- Computer programs; Statistics -- Graphic methods -- Computer programs